(3GdGfTQGM hQaY GdVjb aj SjQI GHh HcQ GdUOjb (B:s (3TNUjJg hYUQg (B/s - (3GdUdGHj(B: (3Ydj eMeO eMeO(B:s 1963- (Beirut : Dar Ibn Kathir, 2003)
Abu Bakr, Caliph, d. 634; caliphs; Islamic Empire; kings and rulers; history; 622-661; biography
Keywords: Abu Bakr, -- Caliph, -- d. 634; Muhammad, -- Prophet, -- d. 632 -- Companions -- Biography; Caliphs -- Biography; Islamic Empire -- History -- 622-750